(untitled) (Global Journal of Management and Business Research, 2019)
This study aims to investigate the effect of some macroeconomic variables namely; Interest rate, Real exchange Rate, Money supply (M2) and Trade Openness on economic growth in Bangladesh. The economic growth was represented by real gross domestic product and interest rate was presented by real interest rate in Bangladesh, Real Exchange Rate was presented by Real effective exchange rate and M2 was the proxy of money supply. The periods taken for the study were from year 1987 to year 2017. The study has been conducted using Augmented Dickey-Fuller Unit Root Test, Phillips Perron Test, Johansen Cointegration Test, Vector Error correction Model and Wald Test. The findings of the Study is, there have long run relationship coming from Real exchange rate, Interest rate, Money supply (M2) and Trade openness to economic growth. Besides these, there have casual short term relationship coming from Trade openness and Money supply (M2) to economic growth in Bangladesh.